Identification and Analysis of Key Residues Involved in Folding and Binding of Protein-carbohydrate Complexes - Shanmugam, N.R. S.; Selvin, J. F. A.; Veluraja, K.; Gromiha, M. Michael (Protein and Peptide Letters, 2018)
Background: Protein-carbohydrate interactions play vital roles in several biological processes in living organisms. The comparative analysis of binding site residues along with stabilizing residues in protein-carbohydrate complexes provides ample insights to understand the structure, function and recognition mechanism. Objective: The main objective of this study is to identify and analyze the residues, which are involved in both folding and binding of the protein-carbohydrate complexes. Methods: We have identified the stabilizing residues using the knowledge of hydrophobicity, longrange interactions and conservation, as well as binding site residues using a distance cutoff of 3.5Å between any heavy atoms in protein and ligand. Residues, which are common in stabilizing and binding, are termed as key residues. These key resides are analyzed with various sequence and structure based parameters such as frequency of occurrence, surrounding hydrophobicity, longrange order and conservation score. Results: In this work, we have identified 2.45% binding site residues in a non-redundant dataset of 1130 complexes using distance-based criteria and 7.07% stabilizing residues using the concepts of hydrophobicity, long-range interactions and conservation of residues. Further, 5.9% of binding and 2.04% of stabilizing residues are common to each other, which are termed as key residues. The key residues have been analysed based on protein classes, carbohydrate types, gene ontology functional classifications, amino acid preference and structure-based parameters. We found that all-β, α+β and α/β have more key residues than other protein classes and most of the KRs are present in β-strands, which shows their importance in stability and binding of complexes. On the ligand side, Lsaccharide has the highest number of key residues and it has a high percentage of KRs in SRs and BRs than other carbohydrate types. Further, polar and charged residues have a high tendency to serve as key residues. Classifications based on gene ontology terms revealed that Lys is preferred in all the three groups: molecular functions, biological processes and cellular components. Key residues have 6 to 9 contacts within the protein and make only one contact with the carbohydrate ligand. These contacts are dominant to form polar-nonpolar contacts followed by the contacts between charged atoms. Further, the influence of sequence and structural parameters such as surrounding hydrophobicity, solvent accessibility, secondary structure, long-range order and conservation score has been discussed. Conclusion: The results obtained in the present work provide deep insights for understanding the interplay between stability and binding in protein-carbohydrate complexes.
Keywords: Protein-carbohydrate complex